1601. Effect of Preemptive Rituximab Therapy on Epstein–Barr Reactivation in Allogenic Hematopoietic Stem Cell Pediatric Transplants. (26th November 2018) - Catho, Gaud; Scheel, Daniel; Teira, Pierre; Renaud, Christian; Kakinami, Lisa; Ovetchkine, Philippe; Autmizguine, Julie
Abstract: Background: Children with Epstein–Barr virus (EBV) viremia after hematopoietic stem cell transplantation (HSCT) are at increased risk of post-transplant lymphoproliferative disease (PTLD). Our aim was to assess whether pre-emptive rituximab reduced EBV-viral load (EBV-VL) and the risk of developing PTLD. Methods: We retrospectively included all children who had a positive EBV-VL within 12 months after an allogenic HSCT (2007–2015) in a single tertiary pediatric hospital. Whole blood EBV-VL was monitored weekly using a real-time PCR, during the first 100 days after HSCT and then monthly until 6 months post-HSCT or until EBV-VL became undetectable. EBV-VL clearance was defined as two negative EBV-VL at least 1 week apart. Pre-emptive rituximab was defined as a treatment administered before the occurrence of PTLD. We determined the impact of pre-emptive rituximab on EBV-VL clearance, using a marginal structural cox model, adjusting for age at transplant, time between transplant and first positive EBV-VL, in-vivo T-cell depletion at induction, value of EBV-VL at the first dose of rituximab, and the EBV-VL value at the current and previous time point. Results: Of 214 children who underwent allogenic HSCT, EBV DNA was detected in 87 (41%) children. Children who received rituximab after diagnosis of PTLD were excluded, leading to a cohort of 78 children. Twenty-two (28%) children received pre-emptive rituximab. Mean (SD) age was similar in both groups (10 [5] year). First post-transplant positive EBV-VL was earlier in the pre-emptive rituximab group (mean of 55 [54] vs. 113 [96] days; P < 0.05) and first positive EBV-VL was higher in the pre-emptive rituximab group (mean of 3.4 [0.6] vs. 3.0 [0.6] log10 /mL; P < 0.05). In adjusted analyses, pre-emptive rituximab was associated with a higher likelihood of EBV-VL clearance (hazard ratio 1.86; 95% confidence interval 1.10–3.14; Figure 1). Of the 10 children who developed PTLD, none had received pre-emptive rituximab. Conclusion: EBV viremia is frequent in children with allogenic HSCT. Our results suggest that pre-emptive rituximab is associated with more rapid EBV-VL clearance. The effect of rituximab on the risk of PTLD needs to be better defined. Disclosures: All authors: No reported disclosures.